2018
DOI: 10.3390/coatings8060215
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Esophageal Stent Materials by a Drug-Eluting Layer for Better Anti-Restenosis Function

Abstract: Abstract:It is generally accepted that stent implantation is the mainstream therapy in clinics for esophageal cancer in the later period. However, the restenosis caused by tumor cells, epithelial cells, and fibroblasts seriously interferes with the stent medical application and limits its long-term services. To address this conundrum, a series of drug-eluting stents were invented and verified to be feasible in the early stage after implantation, but the limited drug loading and good cell compatibility of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…46 Previous studies have shown that stent implantation can cause the formation of endothelialization in the surrounding tissue. [47][48][49] Although the time of stent implantation in intestinal tract is short, there may not be obvious tissue proliferation around the stent. However, the number of epithelial cells and broblasts in intestinal mucosa tissue is increased in the process of intestinal endothelialization.…”
Section: Biocompatibility Of Intestinal Eluting Stentsmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Previous studies have shown that stent implantation can cause the formation of endothelialization in the surrounding tissue. [47][48][49] Although the time of stent implantation in intestinal tract is short, there may not be obvious tissue proliferation around the stent. However, the number of epithelial cells and broblasts in intestinal mucosa tissue is increased in the process of intestinal endothelialization.…”
Section: Biocompatibility Of Intestinal Eluting Stentsmentioning
confidence: 99%
“…However, the number of epithelial cells and broblasts in intestinal mucosa tissue is increased in the process of intestinal endothelialization. 49 While the antibody used in immunohistochemistry can be detected by the detection of cell proliferation and expression of related factors were used to indirectly explore the compatibility of stent on intestinal tissue. In this study, histopathological examination showed that the MAO/PLLA/paclitaxel/Mg-Zn-Y-Nd and PLLA/Mg-Zn-Y-Nd alloy scaffolds did not induce systemic inammation (p > 0.05), while immunohistochemical results showed that degradation products of the MAO/PLLA/ paclitaxel/Mg-Zn-Y-Nd alloy scaffolds signicantly inhibited proliferation of intestinal cells.…”
Section: Biocompatibility Of Intestinal Eluting Stentsmentioning
confidence: 99%
“…In the previous work, we developed a novel 5‐Fu loaded PDA/PEI (PDA/PEI/5‐Fu) coating on the 317L SS surface which was proved to simultaneously inhibit the esophageal tumor cells, epithelial cells and fibroblast adhesion to the surface (Bai et al, ). Nevertheless, the PDA/PEI/5‐Fu coating's effect on pathological cells migration, macrophages adhesion and its mechanism is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous work, we developed a drug loaded coating based on successively assembling poly‐dopamine (PDA) film, poly‐ethyleneimine (PEI) layer and 5‐Fluorouracil (5‐Fu, an effective anti‐cancer drug widely applied in clinics by oral, topical and injection) drug on the clinical esophageal stent material 317L stainless steel (317L SS), and this PDA/PEI/5‐Fu coating had strong functions on promoting the pathological cells (esophageal tumor cells, esophageal epithelial cells and fibroblasts) apoptosis both on the material surface and in the spatial microenvironment (Bai et al, ; Zhang et al, ). Nevertheless, the mechanism and pathway of the functional composite coating inhibiting esophageal cancer‐related pathological cells are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…The biological behaviour was evaluated by fluorescent staining. Esophageal tumor cells (Eca 109) were directly seeded on the surfaces of DLC coatings at a density of 4.0 × 10 3 cells / mL and cultured in standard condition for 1 day [23][24]. Fluorescent images of cell morphology were evaluated by fluorescence microscopy.…”
Section: Characterizationsmentioning
confidence: 99%